From Queer as Folk to Pose, 20 years later: Representations in dispute, from homophobia to transphobia - Rodrigues, André Iribure (2021)
This paper aims to present a diachronic overview of the approaches of two serials broadcast in different periods, in an interval of two decades. The first, entitled Queer as Folk, from 2000, on pay TV, addresses the unstandardized experiences of gay and lesbian sexuality, while the second, Pose, most recently broadcast by streaming, advances in the representations of transexual and transgender minorities, with cuts of race and social class. It is evidenced, from a look at the studies of gender and sexuality, with the contribution of social representations of social psychology and cultural studies, by content analysis, how the visibilities of tensions and negotiations of what escapes heteronormativity within the limits of serial television fiction take place. From the visibility of a gay, white, middle class hegemony with the motto of homophobia, two decades later, we can see the representations of black and vulnerable people socially and economically when facing transphobia.